Report of three imported cases of neurocysticercosis in Guadeloupe. Issue 1 (December 2017) - Blaizot, R.; Melot, B.; Schepers, K.; Nicolas, M.; Gaumond, S.; Poullain, P.; Belaye, L.; Lannuzel, A.; Hoen, B.
Abstract Background Neurocysticercosis is endemic in most countries of Central and South America but has rarely been described in the French West Indies. We aimed to better understand the clinical and radiological presentation of our cases. Case presentation We report three cases of neurocysticercosis in patients living in Guadeloupe, with different clinical and radiological presentations. Conclusion Given the eventuality of autochtonous transmission, the diagnosis should be considered in all patients living in Guadeloupe presenting with seizures.